Challenges in the Treatment of Acute Fulminant Hepatitis B: Case Report and Literature Review - Abdul Rahman Bizri (Mediterranean Journal of Hematology and Infectious Diseases)
Acute hepatitis B is a serious cause of fulminant hepatic failure and subsequent mortality. No established guidelines are currently present for the treatment of this life threatening entity. Several therapeutic options were reported in the literature including the use of lamivudine as well as the more novel nucleoside analogue entecavir. We report an unfortunate case of fulminant hepatitis B that passed away despite intensive care unit management and treatment with entecavir in combination with steroids. Extensive review of the literature about various therapeutic approaches to manage fulminant hepatitis B was conducted. The aim of this report is to emphasize the need for larger more structured studies in order to improve the outcome of the treatment of this entity.